TINJAUAN ASPEK HUKUM PIDANA TERHADAP PELAKSANAAN KEGIATAN USAHA YANG WAJIB MEMILIKI ANALISIS MENGENAI DAMPAK LINGKUNGAN - Mamonto, Roy; Kadir, Yusrianto; Tumuhulawa, Arifin (At-Tanwir Law Review, 2025)
This study examines the criminal law aspects of business activities required to have an Environmental Impact Analysis (EI) based on Law No. 32 of 2009 on Environmental Protection and Management and Government Regulation No. 27 of 2012 on Environmental Permits. EI is mandatory for activities with significant environmental impacts, aiming to identify environmental risks, accommodate public aspirations, and ensure proper impact management. Criminal sanctions are applied as a last resort (ultimum remedium) when administrative sanctions are ineffective. These sanctions aim to educate business actors, protect public interests, and prevent similar violations. The principle of legality is upheld, requiring actions to be based on existing laws and proven wrongdoing. However, the enforcement of environmental criminal law faces challenges, including a lack of understanding among law enforcers about the essence of environmental crimes. This study that strengthening regulations, enhancing law enforcers' capacity, and consistently applying criminal sanctions are necessary to support the successful enforcement of environmental law. These measures are crucial to preserving the environment and ensuring compliance with EI obligations by business actors.